Neurological manifestation of Coeliac disease in Iraqi patients - Shanan Dhair, Mohammed; Makki Ajam, Mustafa (International Journal of Psychosocial Rehabilitation, 2021)
Background: Celiac disease (CD/Non-tropical sprue, gluten-sensitive enteropathy) is a malabsorptive conditioning in which an allergic reaction to the cereal grain-protein gluten (present in wheat, rye, and barley) causes small intestine mucosal injury. Aims: The purpose of the present study was to evaluate neurological manifestations in association with celiac disease. The specific objectives were to study the neurological manifestations of celiac disease. Methods: Seventy-five unselected consecutive patients (32 men, 43 women, mean age 25.51±8.473 years) with histologically proven CD were enrolled and prospectively investigated. The 75 patients were seen in the Department of Gastroenterology outpatient, medical, and neurological wards of Baghdad hospital. All patients were on a gluten-free diet at recruitment, and the median duration of disease was 2.56±1.670. Results: The onset is in the first four decades of life, with a female to male ratio of 2:1. It may be associated with a wide spectrum of neurological manifestations, including cerebellar ataxia, epileptic seizures, dementia, neuropathy, myopathies, and multifocal leucoencephalopathy. We report three teen patients with neurological manifestations related to CD: two with cerebellar ataxia, two with epilepsy, two with carpel tunnel syndrome, two with myopathies, two with peripheral neuropathy, and one with cognitive impairment. The diagnosis of CD was confirmed by serologic tests (antiendomysial, antitransglutaminase antibodies, and antigliadin antibodies) and biopsy of the small intestine. In two patients the neurological symptoms preceded the gastrointestinal abnormalities, and in all of them gluten restriction failed to improve the neurological disability. Conclusion: CD should be ruled out in the differential diagnosis of neurological dysfunction of unknown cause, including ataxia, epilepsy, and dementia. A gluten-free diet, the mainstay of treatment, failed to improve the neurological disability.